Comparison of Duty Cycle Generator Algorithms for SPICE Simulation of SMPS. (30th May 2012) - Abramovitz, Alexander
Abstract : The paper presents and discusses an algorithm for average modeling of the PWM modulator in switch-mode power systems by general purpose electronic circuit simulators such as PSPICE. A comparison with previous theoretical models is conducted. To test the accuracy of the average PWM models comparison to cycle-by-cycle simulation was conducted. The proposed algorithm shows better accuracy than earlier counterparts.